The Influence of Principal's Leadership and Motivation on Teacher Discipline at SD N 121 Hutabargot Julu - Khopipah Nur; Darmilisani Darmilisani; Emi Wakhyuni (Utan Kayu Publishing, 2024)
This research was conducted at one of the public schools, namely SDN 121 Hutabargot Julu Skor. This research analysis aims to determine the leadership and motivation of school principals regarding teacher discipline. The data analysis technique used is an associative research method with the help of the SPSS version 19 program. This research uses multiple linear regression analysis. The sample in this study was 39 respondents. Primary data collection uses a questionnaire. The results of the research show that the leadership variable shows a tcount value of 3.994 ttable of 2.00 with a significant value of 0.002 0.05, so the hypothesis H1 is accepted and H0 is rejected, meaning that leadership has a partially positive and significant effect on teacher work discipline at SD N 121 Hutabargot Julu. The test results for the motivation variable show a tcount value of 4.474 ttable of 2.00 with a significant value of 0.000 0.05, so the hypothesis H2 is accepted and H0 is rejected, meaning that motivation has a partially positive and significant effect on teachers at SD N 121 Hutabargot July. The calculated F value is 36.628 which is greater than 2.79 and the significant value of 0.000 is smaller than 0.05 so it can be concluded that hypothesis 3 is accepted and hypothesis 0 is rejected so it can be concluded that leadership and motivation have a significant effect simultaneously on teachers in elementary schools. N 121 Hutabargot Julu.